Digital Insights Into Nucleotide Metabolism and Antibiotic Treatment Failure - Lopatkin, Allison J.; Yang, Jason H. (Frontiers in Digital Health, 2021)
As antimicrobial resistance continues to grow unchecked, new approaches are needed to study the molecular mechanisms responsible for antibiotic efficacy. Recent advances in digital and experimental technologies reveal new aspects of bacterial physiology that actively contribute to antibiotic-induced cell death in bacterial pathogens. One particularly compelling example is in nucleotide metabolism – in addition to producing nucleic acids necessary for DNA replication and RNA transcription, nucleotide metabolism underlies the formation of primary cellular energy currencies, and recent works that integrate computational analysis with high-throughput experimentation reveal that disruptions to nucleotide metabolism contribute to antibiotic treatment failure in the clinic. Here we review emerging technologies poised to transform understanding into why antibiotics may fail in the clinic with a focus on nucleotide metabolism. We discuss how these technologies led to the discovery that nucleotide metabolism regulates antibiotic drug responses and why these are relevant to human infections. We highlight opportunities for how studies into nucleotide metabolism may enhance understanding of antibiotic failure mechanisms.